Evaluation of reaction kinetics for chemoselective hydrogenation of citral for intensification of citral intermediates using copper-based catalysts - Debtirtha, Banik; Kinage, Anil K.; Vasireddy, Satyam Naidu (Indian Chemical Engineer, 2025)
Citral intermediates’ formation kinetics is studied using non-noble metal catalyst (Cu/SiO2) to evaluate catalyst performance characteristics via chemoselective hydrogenation of citral. The catalyst is synthesised by the precipitation method and characterised using XRD, FESEM and BET surface area analyser. Hydrogenation experiments are carried out using an Autoclave reactor in the temperature range of 80–120°C, pressure range of 10–50 bar and for catalyst loadings of 0.5, 1 and 1.5 g. The intermediates product distribution comprises aldehyde and alcohol formation such as citronellal, nerol and citronellol formation. The performance of the Cu/SiO2 catalyst is evaluated using the parameters such as citral conversion, citronellol selectivity and yield as 96.96%, 95.30% and 92.30%, respectively under optimal conditions of 50 bar, 120°C and 1 g catalyst for the reaction time of 100 min. The absence of internal and external mass transfer limitations is verified using the Carberry number and Weisz-Prater modulus criterion. The intrinsic kinetics of the gas–liquid phase hydrogenation of citral is determined using the Langmuir–Hinshelwood-Hougen-Watson (LHHW) model for citral intermediates formation. The reaction kinetic parameters show that citronellol formation favours by the nerol route compared to citronellal conversion.